College environment andentrepreneurial intentionin high school (REGE Revista de Gestão, 2024)
PurposeThere is no consensus on the most effective way to foster entrepreneurship in educational institutions, and educational policies on entrepreneurial activity differ significantly amidst organizations and contexts. Thus, the objective of this research is to analyze influence of the college environment and entrepreneurial characteristics on the entrepreneurial intention of Brazilian high school/technical students.Design/methodology/approachThe empirical research used partial least squares structural equation modeling (PLS-SEM) and a sample of 384 students of technical courses, such as Administration, Systems Development, Chemistry, Secretariat, among others.FindingsThe proposed model was validated, and the hypotheses were confirmed, proving suitable for high school/technical education. Assessing the high school environment with this model can help determine each organization's strengths and weaknesses and, indeed, the impacts on the ecosystems in which it operates. The results of the multi-group analysis indicate differences concerning the courses as well.Research limitations/implicationsThe main limitations involve non-probabilistic sampling procedures and the collection having been carried out with a single cross-section.Practical implicationsFor managers and teachers, this article presents indicators to qualify the activities of the educational environment, considering teaching activities, extracurricular activities, fairs, actions of teachers and students, among other initiatives.Originality/valueThis research presents a novel analysis of the antecedents that drive student entrepreneurship in an underexplored educational context in a developing country. The results show the necessary conditions for technical schools to foster entrepreneurial activity, feeding innovation ecosystems with entrepreneurial talent.